French Sources of Women’s Education in the XVIIth Century (Training and Practice : Journal of Educational Sciences, 2015)
The study reports the partial results of a wider research which examines the history of women’s and girls’ life and education. In the focus of the research there are those sources, which are originated from the XVIIth century in France and they are printed out as well. Not only the origin of these sources, but also their effects and reception are examined in our study, especially the reception and presentation of French authors from the XVII–XXth centuries in Hungary.Fenelon, Madame Maintenon and the works of other authors had effects on the work of Kelemen Mikes, Andras Fáy, Eötvös József, István Gyertyánfy, and they can be found in the studies of excellent pedagogical minds like Ödön Weszely, Ernő Fináczy and Gyula Kornis.